STATISTICAL OPTIMIZATION OF PROCESS PARAMETERS FOR PRODUCTION OF ALKALINE PROTEASE FROM VIBRIO METSCHNIKOVII NG155 HAVING APPLICATION IN LEATHER INDUSTRY - NANCY GEORGE,; PRAKRAM SINGH CHAUHAN,; NEENA PURI,; NAVEEN GUPTA, (International Journal of Pharma and Bio Sciences, 2014)
Alkaline protease producing microorganism Vibrio metschnikovii NG155, isolated from the soil samples of leather industry, having potential application in dehairing of animal skin was used in this study. To enhance the production of protease by this strain, various physical and nutritional factors were optimized using statistical methods like Plackett Burman and Response Surface Methodology. In accordance with the Plackett Burman design three nutritional variables soyabean meal, wheat gluten meal and cotton seed flour having a significant positive effect on protease production were selected and optimized by Response Surface Methodology. Production of protease was increased considerably (200 Uml-1) in the optimized medium containing 2.46 (%) wheat gluten meal, 2.45 (%) soyabean meal and 1.46 (%) cotton seed flour, leading to an overall 13 fold increase from the unoptimised medium.